Comparison of K-doped and pure cold-rolled tungsten sheets: Microstructure restoration in different temperature regimes. (June 2023) - Lied, Philipp; Pantleon, Wolfgang; Bonnekoh, Carsten; Dürrschnabel, Michael; Bienert, Christian; Hoffmann, Andreas; Reiser, Jens; Rieth, Michael
Abstract: For tungsten in divertor parts of future fusion reactors, a fine-grained microstructure is preferred to reduce its brittle-to-ductile transition temperature and minimize cracking events due to cyclic thermal and mechanical loading. In our ongoing study on tungsten sheets with different degree of deformation by warm- and cold-rolling, the potential of potassium-doping to stabilize the microstructure at high operation temperatures is assessed. Successful production of technically pure and equivalently rolled potassium-doped tungsten sheets up to very high logarithmic strains of 4.6 was already shown in the past with in-depth analysis of the evolution of microstructure and mechanical properties after rolling steps. Our current study investigates the microstructure changes in the same material batch by recovery, recrystallization and grain growth in temperature regimes between 600 °C and 2400 °C. Annealing studies with subsequent microhardness and SEM analysis reveal increased retardation of recrystallization in potassium-doped tungsten with higher rolling strain, but abnormal grain growth at high temperatures is also increased. However, potassium-doped tungsten with low rolling strain shows promising results with much less grain growth than its pure tungsten counterpart. Graphical abstract: Unlabelled Image Highlights: Cold-rolled tungsten sheets heavily prone for extended recovery at low temperatures. K-doping impedes recrystallization and grain growth of W in mid-temperature regime. Increasing rolling strain improves K-bubble dispersion and inhibition of RX/GG. However, high K-bubble dispersion leads to abnormal GG at high temperatures. K-doped W with low rolling strain shows smallest grain size at high temperatures.